Jacques Maritain and Popes Pius XI and XII on the Church-State Relationship - (:unkn) unknown (My University, 2022)
Jacques Maritain (1882-1973) was a French Catholic philosopher, acknowledged as one of the most influential non-clerical Catholics of the twentieth century. During this time, the Catholic Church was experiencing the slow process of political displacement. Maritain and the contemporary popes addressed how the Church should function within the modern context. Both began the century sympathetic to right-leaning governments and political parties that supported the Catholic Church but shifted over time to embrace a less direct approach. This thesis will demonstrate the change over time of Maritain’s position and how it paralleled the positions of Popes Pius XI and Pius XII. Specific focus will be given to the subjects of nationalism, democracy, and human rights. This is historically significant, because Maritain was highly influential and because the questions they sought to resolve remain unsettled. The role of religion on questions on authority, freedom, and human rights is fiercely debated today.
Keywords: Catholic Church; Church-State; Jacques Maritain; Personalism; Pope Pius XI; Pope Pius XII